Clinical manifestation and prevalence of peripheral neuropathy and nerve dysfunction in patients with chronic kidney disease - Babu, M. Madhusudhana; Kiran, M. Ravi; Ravindra, Kavuru; Srinivas, Vaddadi; Kandregula, Padmalatha; Vardhan, R. Vikram; Kumar, Navsk Ravi (International Journal of Research in Medical Sciences, 2017)
Background: Chronic Kidney Disease (CKD) is recognized as a major health problem. Prevalence of CKD is rising continuously; mostly CKD is affecting the elderly aged population and/or patients with diabetes and hypertension. Present study was aimed to explore clinical manifestation and evaluate the prevalence of peripheral neuropathy and peripheral nerve dysfunction in CKD patients attending our hospital with reference to the severity and duration of the CKD. Methods: The present cross sectional study was conducted in 74 patients affected with chronic kidney disease, of different age groups at the medical wards of King George Hospital, Visakhapatnam. The presence of peripheral nerve dysfunction was assessed by nerve dysfunction clinically (motor or sensory symptoms and signs) and electrophysiological nerve conduction studies. Results: Out of 74 patients, 65% of study population was suffering from chronic kidney disease with peripheral nerve dysfunction. The peripheral nerves dysfunction was more prevalent in elder age (>65 years) subjects when compared to subjects with age <65 years. Moreover, the results shown that the rate of prevalence of peripheral nerves dysfunction was observed higher in subjects with longer duration of CKD. Male subjects were affected more when creatinine clearance is <15 ml/minute. Both sexes were affected equally when creatinine clearance is between 30-59 ml/minute. Conclusion: This study enlightens the prevalence and clinical presentation of peripheral nerve dysfunction in patients with CKD. The CKD was found to cause peripheral neuropathy including overt and subclinical neuropathy, of which distal symmetrical sensory motor neuropathy was common in CKD. The prevalence of peripheral neuropathy was directly proportional to duration and severity of CKD.